From fairy rings to fairy chemicals: The story from nature phenomenon to commercial application - Shaolong Liu; Chanjuan Ye; Jie Guo; Da‐gang Chen; Juan Liu; Xin‐qiao Zhou; Bin Jia; Yixiong Zheng; Jing Wu; Hirokazu Kawagishi; Ke Chen; Chuan‐guang Liu (Modern Agriculture)
Abstract Fairy rings are naturally occurring phenomena that are circular or curved clusters of mushrooms that appear in meadows, forests, and other places. In recent decades, significant progress has been made in deciphering fairy chemicals (FCs) involved in the intricate crosstalk between mushrooms and plants. FCs contain three chemical components: 2‐azahypoxanthine (AHX), 2‐aza‐8‐oxohypoxanthine (AOH), and imidazole‐4‐carboxamide (ICA). FCs can enhance the plant's resistance to environmental stresses such as cold, heat, and salt, and can increase crop yields; In addition, it can also have biological activities such as skin barrier improvement, anti‐ageing, and anti‐tumour. This review systematically integrated multiple facets of FCs, encompassing their discovery, the biochemical synthesis pathways giving rise to FCs, the derivatives and compounds originated from FCs, and their emerging applications in agriculture, beauty industry and medical sciences. Moreover, the review also addresses outstanding questions in FCs and future challenges related to plant growth regulators and other compounds, promising a practical and innovative future in agriculture.